Manajemen Mutu Sekolah dalam Pembudayaan Karakter - Evi Kuswandari; Sowiyah Sowiyah; Hasan Hariri (9 772338317006, 2017)
The purpose of this research was to investigate and describe the management of character building through such management functions as planning, organizing, implementing, and evaluating. This research was included in the type of qualitative research, with the data sources of 12 informants. The data were collected in using observation, interview, and documentation. Results of this research showed that: (1) planning to arrange character building program was through designing lesson plan completed with three main activities: intracurricular, cocurricular, and extracurricular, (2) organizing the character building was carried out through formation of a team of teachers in acoordance with their tasks and functions, (3) implementating character building was learner-oriented in understanding concept and habituation of character building, and (4) evaluating management in character building was conducted through daily observation, supported by school community, with an indicator of success that learners were able to instill character building and implement this character building in their daily life.Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan manajemen pembudayaan karakter melalui fungsi manajemen seperti perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Penelitian ini termasuk dalam jenis penelitian kualitatif, dengan sumber data 12 informan. Tekhnik pengumpulan data dilakukan menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukan bahwa: (1) perencanaan menyusun program pembudayaan karakter adalah melalui rancangan rencana pelaksanaan pembelajaran (RPP) yang dilengkapi dengan tiga kegiatan utama: intrakulikuler, ko-kulikuler, dan ekstrakulikuler, (2) pengorganisasian pembudayaan karakter ini di lakukan dengan pembentukan tim guru, sesuai tugas dan fungsinya, (3) pelaksanaan pembudayaan karakter berorientasi pada pemahaman konsep dan pembiasaan pembudayaan karakter, dan (4) evaluasi manajemen pembudayaan karakter dilakukan melaui pengamatan harian, didukung oleh masyarakat. sekolah, indikator keberhasilan peserta didik mampu menanamkan pembudayaan karakter dan melaksanakan pembudayaan karakter dalam kehidupan sehari-hari.Kata Kunci : manajemen mutu sekolah, pembudayaan, pendidikan karakter